2005
DOI: 10.1159/000086911
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormalities in sperm from infertile men with normal somatic karyotypes: asthenozoospermia

Abstract: The aim of aneuploidy evaluation in spermatozoa from patients presenting spermatogenesis defects is to identify a relationship between meiotic errors and quantitative or qualitative alterations of spermatogenesis. During the past ten years, the use of fluorescence in situ hybridization (FISH) has permitted the determination of the frequency of numerical chromosome aberrations in different clinical situations. It has been established that infertile males with reduced sperm count and a normal constitutional kary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…Although low motility was observed for RobT patients (compared with 46,XY patients), the increased aneuploidy rate was probably due to occurrence of the translocation. An increased aneuploidy rate was observed only for patients with <5% motile sperm (35)(36)(37).…”
Section: Tablementioning
confidence: 96%
“…Although low motility was observed for RobT patients (compared with 46,XY patients), the increased aneuploidy rate was probably due to occurrence of the translocation. An increased aneuploidy rate was observed only for patients with <5% motile sperm (35)(36)(37).…”
Section: Tablementioning
confidence: 96%
“…Whereas the link between a low sperm count and an increased risk of aneuploidies in spermatozoa is widely accepted, the relationship between chromosome abnormalities and sperm motility is more controversial (7,30). Although some investigators have reported a certain correlation between the two parameters (26,(30)(31)(32), especially for sex chromosomes, other studies have failed to find any relationship (25,27,33).…”
Section: Indications For a Fish Analysismentioning
confidence: 99%
“…Several investigators have reported a high number of chromosomal abnormalities in spermatozoa from patients with an altered seminogram (4)(5)(6)(7)(8). This result has been related to the diminished fertility of the patients and to an increased risk for the transmission of abnormalities.…”
mentioning
confidence: 99%
“…However, it cannot be excluded that CCR carriers are more prone to exhibit ICE because of the substantially high numbers of chromosomes involved in rearrangement, especially with regard to the ongoing debate on the influence of chromosomal rearrangements on the proper meiotic behaviour of other chromosomes. It has also been documented that increased aneuploidy rates can be present in spermatozoa of males with decreased sperm seminological parameters (OAT -oligo-, astheno-, teratozoospermia) (Hristova et al 2002, Tempest & Griffin 2004, Machev et al 2005, Miharu 2005, Rives 2005, Tang et al 2010. A large majority of findings indicate a well-defined link between ICE presence and oligozoospermia, while no such clear association has been observed in cases of astheno-or teratozoospermia (Tempest & Griffin 2004, Machev et al 2005, Miharu 2005, Rives 2005).…”
Section: Discussionmentioning
confidence: 99%